2015
DOI: 10.1093/jmammal/gyv049
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphologic data reveal multiple species inPeromyscus pectoralis

Abstract: DNA sequence and morphometric data were used to re-evaluate the taxonomy and systematics of . Phylogenetic analyses (maximum likelihood and Bayesian inference) of DNA sequences from the mitochondrial cytochrome- gene in 44 samples of indicated 2 well-supported monophyletic clades. The 1st clade contained specimens from Texas historically assigned to; the 2nd was comprised of specimens previously referable to ,, and obtained from northern and eastern Mexico. Levels of genetic variation (~7%) between these 2 cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…Based on the logic presented in Bradley and Baker (2001), our results revealed that GG3 (furvus from the type locality Xalapa, Veracruz and its surroundings) and GG2 (angustirostris from Hidalgo, Puebla and locations further NW in Veracruz) would appear to be subspecies. The genetic distances between GG2 and GG3 are similar to that reported by Bradley et al (2015) for two subspecies (ranging from 1.77 % in P. p. laceianus to 2.21 % in P. p. pectoralis). Similarly, Lorenzo et al (2016) use a K2P genetic distance of 2.08-3.65% to define two subspe-cies of P. zarhynchus in Chiapas (P. z. zarhynchus and P. z. cristobalensis).…”
Section: Discussionsupporting
confidence: 84%
“…Based on the logic presented in Bradley and Baker (2001), our results revealed that GG3 (furvus from the type locality Xalapa, Veracruz and its surroundings) and GG2 (angustirostris from Hidalgo, Puebla and locations further NW in Veracruz) would appear to be subspecies. The genetic distances between GG2 and GG3 are similar to that reported by Bradley et al (2015) for two subspecies (ranging from 1.77 % in P. p. laceianus to 2.21 % in P. p. pectoralis). Similarly, Lorenzo et al (2016) use a K2P genetic distance of 2.08-3.65% to define two subspe-cies of P. zarhynchus in Chiapas (P. z. zarhynchus and P. z. cristobalensis).…”
Section: Discussionsupporting
confidence: 84%
“…With the utilization of molecular data and the expansion of species concepts, the content of the genus Peromyscus has been expanded from 53 species recognized by Carleton (1989) and Musser and Carleton (1993), to 56 species recognized by Musser and Carleton (2005), to 66 species recognized by Pardiñas et al (2017) and to 78 species currently recognized in the Mammal Diversity Database (Mammal Diversity Database 2020). Over 20 new species of Peromyscus have been recognized just in the past 10 years (Ávila-Valle et al 2012;Bradley et al 2014Bradley et al , 2015Bradley et al , 2019Pérez-Consuegra and Vazquez-Domínguez 2015;Greenbaum et al 2019;Lorenzo et al 2016;Álvarez-Castañeda et al 2019;López-González et al 2019;Léon-Tapia et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We only included records for which at least one museum voucher existed, even though the museum number may or may not have been provided in the publication. Data were included only from species descriptions or recent taxonomic revisions (e.g., Bradley et al 2014, 2015; Mathis et al 2013b, b; Mathis et al 2014). Third, data from a catch-and-release project conducted by the first author in the SMO between 2021 and 2022.…”
Section: Methodsmentioning
confidence: 99%